Prediction of the Stress Wave Amplification Factor of a Spherical Blast Source Using Numerical Simulations - Rehman, J. U.; Nguyen, C. N.; Nguyen, T. A.; Vo, T. C.; Nguyen, T. K.; Nguyen, V. Q. (Engineering, Technology & Applied Science Research, 2022)
A typical blast wave attenuation curve presents a relationship between Peak Particle Velocity (PPV) at the surface of a geologic profile and distance. As the stress wave is amplified at the free-field boundary, the attenuation curve at the surface is always larger than the within media profile curve. Measurements are made at the rock’s surface and test blasts are always conducted to ensure the safety of underground existing structures. In order to design underground blasting, the recorded PPVs are then reduced by a factor of 2. In this paper, particle velocity amplification was studied by using numerical simulation, and the difference between PPV at the surface and within media profiles is quantified. The amplification factor depends upon source depth, incidence angle, and Poisson’s ratio of the media. It is calculated as the ratio of the magnitude of PPV at the surface of the media to the within media profile. According to the parametric study, the amplification factor for a uniform medium increases with increasing source depth, while the amplification factor decreases with increasing Poisson’s ratio. Considering a three-layer model with a source depth of 30m, the amplification factor is high for low incident angles and low for higher incident angles. The range varies between 1.5 to 2.1.